(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
Three-dimensional structural characteristics of TiO₂ photoanodes play a crucial role in determining the performance of dye-sensitized solar cells (DSSCs). In this work, single-layer and bilayer TiO₂ photoanodes were comparatively investigated using industrial microfocus X-ray tomography. The approach enabled volumetric visualization of internal architecture, thickness distribution, interfacial integrity, and defect formation not accessible by conventional two-dimensional techniques.